Fairness in Home Healthcare: can patient-centered and nurse-centered measures concur to the same goals?. Issue 10 (2022) - Bonomi, V.; Mansini, R.; Zanotti, R.
Abstract: In commercial transactions, the main goal of a company is to minimize costs or maximize profits. In the last years, the importance of optimizing alternative goals has become more and more critical, especially in those domains where business activities are focused on providing services to products (by integrating them into the product itself - servitization), or more importantly, to persons (healthcare systems). In these contexts, the satisfaction of customers (patients) is as relevant as that of employees (professional care givers) to guarantee an effective and efficient level of service. The introduction of the concept of fairness allows to separately consider the optimization of employee-centered and customer-centered measures, possibly working out positive interactions among the two categories. In this paper, we analyze several measures of fairness both patient-centered and nurse-centered within a vehicle routing problem where nurses are routed to visit patients at their homes. We provide the mathematical formulations for different fairness measures and compare their results on a set of benchmark instances drawing some interesting conclusions on their interactions and possible impact in terms of costs.